Paraburkholderia sabiae administration alters zebrafish anxiety-like behavior via gut microbial taurine metabolism - Ichikawa, Shunsuke; Abe, Reimi; Fujimoto, Haruka; Higashi, Koushi; Zang, Liqing; Nakayama, Hiroko; Matsuoka, Izumi; Shimada, Yasuhito (Frontiers in Microbiology, 2023)
Interventions to the gut microbiome manipulate the gut–brain axis and could be useful in the treatment of anxiety and depression. In this study, we demonstrated that administration of the bacterium Paraburkholderia sabiae reduces anxiety-like behavior in adult zebrafish. P. sabiae administration increased the diversity of the zebrafish gut microbiome. Linear discriminant analysis Effect Size (LEfSe) analysis revealed that the populations of Actinomycetales including Nocardiaceae, Nocardia, Gordoniaceae, Gordonia, Nakamurellaceae, and Aeromonadaceae were reduced, whereas those of Rhizobiales including Xanthobacteraceae, Bradyrhizobiaceae, Rhodospirillaceae, and Pirellulaceae were increased in the gut microbiome. Functional analysis using Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt2) predicted that P. sabiae administration altered taurine metabolism in the zebrafish gut, and we demonstrated that P. sabiae administration increased the taurine concentration in the brain. Since taurine functions as an antidepressant neurotransmitter in vertebrates, our results suggest that P. sabiae could improve anxiety-like behavior in zebrafish via the gut-brain axis.